2018
DOI: 10.1177/0963689718766328
|View full text |Cite
|
Sign up to set email alerts
|

Sequential combined Treatment of Pifithrin-α and Posiphen Enhances Neurogenesis and Functional Recovery After Stroke

Abstract: Objective:Although cerebral ischemia can activate endogenous reparative processes, such as proliferation of endogenous neural stem cells (NSCs) in the subventricular zone (SVZ) and subgranular zone (SGZ), the majority of these new cells die shortly after injury and do not appropriately differentiate into neurons, or migrate and functionally integrate into the brain. The purpose of this study was to examine a novel strategy for treatment of stroke after injury by optimizing the survival of ischemia-induced endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Different strategies have been developed in order to promote neurogenesis and regeneration 27,28 . Moreover, in the field of stem cell therapy, the preconditioning of MSCs, culturing them in specific conditions or through the addition of different compounds, may improve their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies have been developed in order to promote neurogenesis and regeneration 27,28 . Moreover, in the field of stem cell therapy, the preconditioning of MSCs, culturing them in specific conditions or through the addition of different compounds, may improve their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the disrupted nerve tracts, the motor and sensory dysfunction persisted for at least 28 days after the stroke. Previous studies have shown the therapeutic effect of endogenous NSCs on MCAO model [ 28 ]. However, no in situ or migrated endogenous NSCs were found in or around the infarct in the brainstem stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of brain atrophy in stroke animals using Giemsa staining 4 weeks post stroke, brains were harvested and subjected to Giemsa staining as described previously (Turcato et al, 2018). Briefly, post-stroke 4-week brain sections (25 mm) were mounted on PLL-coated slides.…”
Section: Systemic Peptide Treatmentmentioning
confidence: 99%